“Onko tämä sitä creativitya”: A Case Study of the Functions of Code Switching by IB students in a WhatsApp Conversation - Salminen, Jenna (My University, 2016)
This thesis is a case study which sets out to identify the main functions of code switching in a group of eleven International Baccalaureate students’ computer mediated communication through an application called WhatsApp. Code switching has in this thesis been defined as the alteration between two languages. The aim of the study was to identify the discourse functions that switching from Finnish to English serves in this particular discourse group and to find out what sort of individual differences within the group could be identified. As the students in the International Baccalaureate Programme use English in their studies but speak Finnish as their native language, it was hypothesized that code switching would be common and that code switching as an expression of group solidarity would be among the most common functions. All instances of code switching were identified and then categorized according to a new framework which was formed for the purposes of the present study. The framework is based on Gumperz (1982), Cheng (2003), Malik (1994) and Leppänen et al (2011). A total of 334 cases of code switching and eight categories of functions were found. The most common function for code switching was the category of interjections, habitual expressions and sayings (24.0%). Following the group’s norm through code switching to a specific variety of English was the second most common function (18.3%), followed by a lack of expression or register in the main code (18.0%). All speakers used varying amounts of code switching.